Introduktion av buskskikt i ungskogar - Lymer, Richard (SLU/Landscape Management, Design, and Construction (until 121231), 2010)
Young stands in urban forests often lack a shrub layer, though shrubs play an important structural and biological role in forests. All layers interact with one another to form a multilayered stand, in which shrubs have a vital role. In this diploma thesis, theoretical models for forest dynamics are compared with four reference stands to detect factors, and principals for introduction of shrubs in young stands. In these stands four different ways of introduction were found. In one trees and shrubs were planted together at the same time. Shrubs spontaneous spread under a canopy of mature forest, in another. In a third stand an open shrubland became overgrown by trees into a forest. In the fourth stand the shrublayer was actively planted into a young forest. Shrubs constitution and growing properties decide in which stand they are able to establish. Different types of shrub have different tolerances to light and shadow. This makes them suitable for different types of light conditions. Shrubs with longitudinal length growth characteristics, is likely to compete with trees to seek light. While shrubs with lateral or bastion growth will be broaden in shape. Shrublayer is formed in a late stage of the theoretical models that describes natural forest development. One model calls this the understorey reinitiations stage. These light conditions are what one has to obtain to introduce shrubs in a younger stand. One needs to clear a stand to get the properties of an older stage, if one wants to establish a shrub layer. A stable multilayered stand with a vital shrub layer is possible to create in a young stand, that doesn't need constant management. Such a stand can provide structural-and biological amenities for urban recreation despite it's young age.